The immunological activities and transcriptome analysis of a potent small-molecule immunomodulator - Yasser Tabana; Shima Shahbaz; Dinesh Babu; Marawan Ahmed; Tae Chul Moon; Frederick G. West; Richard Fahlman; Arno G. Siraki; Shokrollah Elahi; Khaled Barakat (Elsevier, 2024)
The use of small molecules in immunotherapy is a promising and rapidly growing field with the potential to revolutionize the way we treat a wide range of immunological diseases. The success stories of using small molecules in immunotherapy have been highlighted with many drugs, such as checkpoint inhibitors, which have achieved significant success in treating several types of tumors. However, despite this success, the development of small molecules for immunotherapy is still in its infancy, and there are many challenges that remain to be addressed. In a recent study, our laboratory reported the immunostimulatory effect of a small molecule (Compound A) (A). In this paper, we studied a derivative of this molecule (Compound B) (Fig. 1B). and analysed its physiochemical properties, immunological activities, and transcriptome profiling. Compound B exhibited acceptable metabolic stability and no toxicity against PBMCs. We also demonstrated that Compound B was capable of modulating the immune system by inducing pro-inflammatory cytokines and promoting T-cell proliferation. RNAseq results showed that Compound B was able to significantly upregulate genes involved in stimulating the immune response pathways. Our findings suggest that Compound B may serve as a promising therapeutic agent to modulate the immune system. The identification and validation of the molecular targets responsible for its immunological activities are underway.